A single intranasal dose of human mesenchymal stem cell-derived extracellular vesicles after traumatic brain injury eases neurogenesis decline, synapse loss, and BDNF-ERK-CREB signaling - Kodali, Maheedhar; Madhu, Leelavathi N.; Reger, Roxanne L.; Milutinovic, Bojana; Upadhya, Raghavendra; Attaluri, Sahithi; Shuai, Bing; Shankar, Goutham; Shetty, Ashok K. (Frontiers in Molecular Neuroscience, 2023)
An optimal intranasal (IN) dose of human mesenchymal stem cell-derived extracellular vesicles (hMSC-EVs), 90 minutes post-traumatic brain injury (TBI), has been reported to prevent the evolution of acute neuroinflammation into chronic neuroinflammation resulting in the alleviation of long-term cognitive and mood impairments. Since hippocampal neurogenesis decline and synapse loss contribute to TBI-induced long-term cognitive and mood dysfunction, this study investigated whether hMSC-EV treatment after TBI can prevent hippocampal neurogenesis decline and synapse loss in the chronic phase of TBI. C57BL6 mice undergoing unilateral controlled cortical impact injury (CCI) received a single IN administration of different doses of EVs or the vehicle at 90 minutes post-TBI. Quantifying neurogenesis in the subgranular zone-granule cell layer (SGZ-GCL) through 5'-bromodeoxyuridine and neuron-specific nuclear antigen double labeling at ~2 months post-TBI revealed decreased neurogenesis in TBI mice receiving vehicle. However, in TBI mice receiving EVs (12.8 and 25.6 x 109 EVs), the extent of neurogenesis was matched to naive control levels. A similar trend of decreased neurogenesis was seen when doublecortin-positive newly generated neurons were quantified in the SGZ-GCL at ~3 months post-TBI. The above doses of EVs treatment after TBI also reduced the loss of pre-and post-synaptic marker proteins in the hippocampus and the somatosensory cortex. Moreover, at 48 hours post-treatment, brain-derived neurotrophic factor (BDNF), phosphorylated extracellular signal-regulated kinase 1/2 (p-ERK1/2), and phosphorylated cyclic AMP response-element binding protein (p-CREB) levels were downregulated in TBI mice receiving the vehicle but were closer to naïve control levels in TBI mice receiving above doses of hMSC-EVs. Notably, improved BDNF concentration observed in TBI mice receiving hMSC-EVs in the acute phase was sustained in the chronic phase of TBI. Thus, a single IN dose of hMSC-EVs at 90 minutes post-TBI can ease TBI-induced declines in the BDNF-ERK-CREB signaling, hippocampal neurogenesis, and synapses.